Gyrfalcon Prey Abundance and Their Habitat Associations in a Changing Arctic - Michaela Gustafson; Jennifer D. McCabe; Brian W. Rolek; Travis L. Booms; Michael T. Henderson; Leah Dunn; David L. Anderson; Jennyffer Cruz (Ecology and Evolution)
ABSTRACT Arctic habitats are changing rapidly and altering trophic webs and ecosystem functioning. Understanding how species' abundances and distributions differ among Arctic habitats is important in predicting future species shifts and trophic‐web consequences. We aimed to determine the habitat–abundance relationships for three small herbivores on the Seward Peninsula of Alaska, USA by fitting data from 983 point counts (collected during 2019, 2021, and 2022) with N‐mixture models that account for imperfect detection. These herbivore species, Willow Ptarmigan (Lagopus lagopus), Rock Ptarmigan (L. muta), and Arctic ground squirrels (Urocitellus parryii), are fundamental to tundra food webs, and primary prey for Arctic raptors including Gyrfalcons (Falco rusticolus). Second, we aimed to map herbivore densities within Gyrfalcon breeding territories. Third, we aimed to evaluate whether Gyrfalcons were more likely to occupy territories with higher prey densities using a multi‐season occupancy model coupled with occupancy observations from helicopter surveys conducted during 2016–2022 at 97 Gyrfalcon territories. We found that male Willow Ptarmigan were more abundant in areas with greater cover of tundra, tall shrubs, and tussock tundra. Conversely, male Rock Ptarmigan were more abundant in areas with greater cover of sparse vegetation and tundra. Arctic ground squirrels were more abundant at higher elevations with greater cover of sparse vegetation and low shrubs. Willow Ptarmigan were widespread within Gyrfalcon breeding territories, whereas Rock Ptarmigan and Arctic ground squirrels had patchier distributions with few areas of high abundance. Lastly, Gyrfalcons were more likely to occupy territories with higher densities of Willow Ptarmigan and Arctic ground squirrels. As the Artic continues to warm, Rock Ptarmigan and Arctic ground squirrels may be vulnerable to ongoing shrub encroachment, whereas Willow Ptarmigan may benefit. By tying abundances of three prey to Gyrfalcon occupancy, our results contribute to understanding potential impacts on higher levels of this Arctic trophic web.